The Buddhist Concept as a Solution to the Environmental Crisis - Makcharoen, Pairor (Journal of International Buddhist Studies, 2016)
The Buddhist concept and the mainstream economy concept derive from “craving”, both of them are totally different in every dimension. Buddhist concept can cover flaws and propose better ways to conserving the environment and solving environmental crisis. The Buddhist concept is proposed to replace mainstream economy concept and the paradigm shift should be implemented as fast as possible. New paradigm shift will systematically lead to the new form of economy and society which are environmentally friendly, induce sustainable development and strike a balance between body and mind later.